2015
DOI: 10.1088/2040-8978/18/1/015502
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal nonlinear optical response of graphene oxide-Au nanoparticles dispersed in different solvents

Abstract: In this paper, we report on the preparation of graphene oxide and graphene oxide-Au nanodispersions in various solvents, such as water, DMF (N,N-dimethylformamide) and NMP (N-methyl-2-pyrrolidone). Optical, structural and nonlinear optical properties of all the samples have been studied. The nonlinear optical properties have been measured using the z-scan technique. It is shown that the incorporation of Au nanoparticles can greatly improve the nonlinear optical properties of graphene oxide. More importantly, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…By lateral displacement of the aperture from the beam propagation axis, the open-aperture configuration, the nonlinear absorption coefficient will be measured by recording the entire signal beam. Without the aperture, the induced tiny distortions by the feeble n 2 -dependent lens are insignificant and the changes of the signal beam power are only due to the NLO absorption of the sample [62]. The required curve equations for fitting on the normalized transmittance data and finding the NLO constants [63] can be theoretically obtained by describing the propagation of laser beam in the lens-like media by a suitable model [64].…”
Section: Resultsmentioning
confidence: 99%
“…By lateral displacement of the aperture from the beam propagation axis, the open-aperture configuration, the nonlinear absorption coefficient will be measured by recording the entire signal beam. Without the aperture, the induced tiny distortions by the feeble n 2 -dependent lens are insignificant and the changes of the signal beam power are only due to the NLO absorption of the sample [62]. The required curve equations for fitting on the normalized transmittance data and finding the NLO constants [63] can be theoretically obtained by describing the propagation of laser beam in the lens-like media by a suitable model [64].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the literature supports both explanations for the change in SPR position of AuNPs. Fakhri et al [73] reported nonlinear optical responses of graphene oxide-Au nanoparticles dispersed in different solvents. The authors recorded the maximum absorption peak in the UV-Vis Au / GO spectrum at 527 nm.…”
Section: Interaction Between Graphene Oxide Reduced Graphene Oxide An...mentioning
confidence: 99%
“…Using Eq. (10), which assumes pump and Stokes waves at its input, we examine the Stokes (n = −1) field amplitude…”
Section: Small-signal Forward Brillouin Gainmentioning
confidence: 99%
“…By comparison, nonlocal nonlinearities require a mechanism by which the optical fields in one location affect the optical response in another location. Nonlocal response has been studied in the context of thermally induced effects [2][3][4], as well as more exotic systems such as nematic liquid crystals [5], trapped atoms [6], Rydberg gases [7], plasmonic systems [8,9], and graphene [10]. All of these interactions are the result of transport mechanisms, such as heat, electric charge, or atoms, that mediate the optical response over an extended distance.…”
Section: Introductionmentioning
confidence: 99%